Finite element analysis of wear and deformation in casing rings for centrifugal pumps - Susilo Handoko; Regan Rahadian P; Hafid Suharyadi; Totok Widiyanto (Politeknik Negeri Lhokseumawe, 2025)
The wear and deformation of critical components in centrifugal pumps, such as wear-casing rings, can be caused by the influence of operational lifetime and varying boundary conditions. To enhance the accuracy of wear and deformation predictions, this study integrates finite element analysis (FEA) with detailed field measurement data, including material wear rates and load conditions. The boundary conditions were applied to the CAD model of the wear-casing ring under varying operational loads. The simulation results indicate that the wear casing ring experiences a maximum deformation of 0.0037545 mm, with an estimated lifespan of 5.571 × 10⁷ cycles under normal loading and 0.5517 × 10⁷ cycles under doubled loading conditions. The installation clearance of the wear casing ring is 0.38 mm, with a tolerance of 0.05 mm. The deformation results fell within the acceptable limits for continued use, meeting the clearance standard. The contributions of this study lie in providing more precise wear predictions and insights into wear ring performance and an applicable predictive maintenance method that can be used to improve pump reliability and reduce maintenance costs.